Mechanically-enhanced integrated three-dimensional micro-nanofiber scaffold and preparation method thereof

Through electrospinning, gas foaming, sol injection and freeze-drying, a mechanically enhanced integrated three-dimensional micro-nanofiber scaffold was prepared, which solved the problems of low mechanical properties and difficulty in functional processing in the prior art, and achieved enhanced mechanical properties and multifunctional implication of the scaffold.

CN119499446AActive Publication Date: 2025-02-25DONGHUA UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411651864.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The three-dimensional micro-nanofiber brackets obtained by the existing gas foamed micro-nanofiber membrane have problems such as low mechanical properties, easy to delaminate, loose fiber accumulation, and poor conformity. The post-processing is difficult, making it difficult to perform functionalization of the opposite sex on both sides.

Method used

The preparation methods of electrospinning, gas foaming, sol injection and freeze-drying are adopted. By mixing hydrophobic and hydrophilic medical polymer materials, a micro-nanofiber membrane is formed, and foamed with foaming liquid is used. Then, sol B is filled and freeze-dried, forming a mechanically enhanced integrated three-dimensional micro-nanofiber scaffold.

Benefits of technology

It significantly enhances the mechanical properties of the three-dimensional micro-nanofiber bracket, the overall structure is more stable, not easy to layer, has better and more controllable surface after-treatment characteristics, which can easily and quickly impart versatility to the bracket and expand the application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499446A_ABST
    Figure CN119499446A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and discloses a mechanically-enhanced integrated three-dimensional micro-nanofiber scaffold and a preparation method thereof. The preparation method comprises the following steps: carrying out electrostatic spinning on hydrophilic and hydrophobic high polymer materials to obtain a micro-nanofiber membrane, foaming by using a sol-containing foaming solution to obtain a three-dimensional micro-nanofiber scaffold, filling the sol, and freeze-drying to obtain the mechanically enhanced integrated three-dimensional micro-nanofiber scaffold. The three-dimensional micro-nano fiber material and the freeze-drying stent in the stent form a continuous integrated interpenetrating network structure, the integrity is good, layering is not prone to occurring, the mechanical property is remarkably enhanced, the stent has more excellent and controllable surface post-treatment characteristics, and particularly, the stent can be conveniently and rapidly endowed with multifunctionality through two-face anisotropic treatment. Meanwhile, during application, the thickness can be flexibly and conveniently regulated and controlled in a press fit mode, so that different medical requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold and a preparation method thereof. Background Art

[0002] Three-dimensional micro-nano fiber scaffolds have the characteristics of high porosity, water absorption, permeability, high specific surface area, and a structure similar to the extracellular matrix. They have great potential and broad prospects in the biomedical field, such as tissue engineering scaffolds, guided bone regeneration membranes, periodontal membranes, etc.

[0003] Most of the existing electrospun three-dimensional micro-nano fiber scaffolds are obtained by extending the spinning time and continuously stacking nanofibers. This method has the disadvantages of low preparation efficiency, easy stratification of scaffolds, and difficulty in improving porosity. The preparation of three-dimensional micro-nano fiber scaffolds by stacking fiber membranes layer by layer can overcome the above-mentioned disadvantages of difficulty in improving porosity, but there are still problems of low preparation efficiency and easy stratification between membranes.

[0004] Gas foaming is a simple and efficient three-dimensional scaffold preparation technology that can quickly expand micro-nano fiber membranes into three-dimensional micro-nano fiber scaffolds. It has the advantages of low cost and convenient operation, and has received widespread attention in recent years. However, practice has shown that the three-dimensional micro-nano fiber scaffolds obtained from gas-foamed micro-nano fiber membranes still have problems such as low mechanical properties, easy stratification, loose fiber stacking, and poor conformality. Moreover, post-processing is difficult and it is not easy to perform anisotropic functionalization on both sides, which makes the three-dimensional scaffolds obtained by gas foaming have a single functional level, limiting its scope of application. Summary of the invention

[0005] The purpose of the present invention is to provide a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold and a preparation method thereof, so as to solve the above-mentioned problems existing in the three-dimensional micro-nano fiber scaffold obtained by the existing gas foaming micro-nano fiber membrane.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, comprising the following steps:

[0008] A hydrophobic medical polymer material, a hydrophilic medical polymer material and a solvent are mixed to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning to obtain a micro-nano fiber membrane;

[0009] The micro-nano fiber membrane is foamed with a foaming liquid to obtain a three-dimensional micro-nano fiber scaffold;

[0010] The three-dimensional micro-nano fiber scaffold is injected with sol B and then freeze-dried to obtain a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold;

[0011] Wherein, the foaming liquid comprises sol A and sodium borohydride; the sol A comprises one or more of gelatin sol, GelMA sol and hyaluronic acid sol;

[0012] The sol B includes one or more of gelatin sol, GelMA sol, silk fibroin sol, hyaluronic acid sol, and chitosan sol.

[0013] Preferably, in the above-mentioned method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the hydrophobic medical polymer material includes one or more of polycaprolactone, polylactic acid, poly-L-lactic acid, poly-D-lactic acid, polylactic acid-hydroxyacetic acid copolymer, and poly-L-lactide-caprolactone; the hydrophilic medical polymer material includes one or more of collagen, gelatin, silk fibroin, chitosan, hyaluronic acid, polyvinyl alcohol, polyethylene glycol, and polyethylene oxide.

[0014] Preferably, in the above-mentioned method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the parameters of the electrospinning are: spinning voltage is 17-20 kV; spinning distance is 12-16 cm; injection speed is 1-1.5 mL / h; needle model is 21-24 G; receiving drum speed is 100-500 rpm.

[0015] Preferably, in the above-mentioned method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the mass concentration of the sol A is 0.01-5%; the concentration of sodium borohydride in the foaming liquid is 0.1-1 mol / L.

[0016] Preferably, in the above method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the foaming time is 10 to 60 minutes.

[0017] Preferably, in the above method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the mass concentration of the sol B is 0.1-20%.

[0018] Preferably, in the above-mentioned method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the injection filling method is: using a syringe to extract sol B and then injecting it into the three-dimensional micro-nano fiber scaffold; the volume ratio of the sol B to the volume of the three-dimensional micro-nano fiber scaffold is 1-5 mL: 1-4 cm 3 .

[0019] Preferably, in the above-mentioned method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the freeze-drying includes freezing and freeze-drying; the freezing temperature is -20°C; the freezing time is 12 to 16 hours; the freeze-drying temperature is -50 to -80°C; and the freeze-drying time is 24 to 48 hours.

[0020] The present invention also provides a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared by a method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold.

[0021] The present invention also provides an application of a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold in biomedical materials.

[0022] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The mechanically enhanced integrated three-dimensional micro-nano fiber scaffold of the present invention, wherein the three-dimensional micro-nano fiber material and the freeze-dried scaffold form a continuous integrated interpenetrating network structure, has good integrity and is not easy to delaminate. Compared with the three-dimensional micro-nano fiber scaffold prepared by traditional gas foaming, the mechanical properties are significantly enhanced.

[0024] (2) The freeze-dried porous scaffold formed after sol filling in the present invention enhances the mechanical properties and barrier properties of the three-dimensional micro-nano fiber material, making the overall structure of the material more stable and not easy to delaminate. It has more excellent and controllable surface post-treatment characteristics, especially two-sided anisotropic treatment, which can easily and quickly give the scaffold multifunctionality, solving the defect of traditional gas foaming scaffolds that are difficult to treat two-sided anisotropic treatment due to low mechanical properties, and expanding the scope of application. At the same time, the thickness can be flexibly and conveniently adjusted by pressing during application to meet different medical needs.

[0025] (3) The present invention adds sol to the foaming liquid. On the one hand, the foaming medium is optimized. The sol effectively dissolves and evenly disperses sodium borohydride, and optimizes the formation and stability of bubbles through its inherent viscosity and stability, thereby ensuring the uniformity of the pore structure and mechanical properties of the three-dimensional scaffold; on the other hand, the foaming process can be regulated. By precisely controlling the concentration of the sol, the decomposition rate of sodium borohydride is regulated to ensure the controllability and stability of the pore structure of the three-dimensional scaffold. The polymer molecules in the sol and the two-dimensional fiber membrane form a preliminary three-dimensional network structure through physical interaction or chemical bonding. As the foaming process proceeds, the expansion and stability of the bubbles further enhance this physical or chemical bonding, providing preliminary mechanical support for the scaffold.

[0026] (4) The present invention adopts the preparation method of electrospinning, gas foaming, sol injection and freeze drying, which is simple to operate, short in process, low in cost and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0028] Figure 1 It is a schematic diagram of the preparation process of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffold of the present invention;

[0029] Figure 2 This is an appearance diagram of the micro-nano fiber membrane obtained in step (1) of Example 1;

[0030] Figure 3 This is an appearance diagram of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared in Example 1;

[0031] Figure 4 This is an appearance diagram of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared in Example 1 after lamination;

[0032] Figure 5 This is a scanning electron microscope image of the micro-nano fiber membrane prepared in step (1) of Example 1;

[0033] Figure 6 This is a scanning electron microscope image of the upper surface of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared in Example 1;

[0034] Figure 7 This is a scanning electron microscope image of the interior of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared in Example 1;

[0035] Figure 8 This is an appearance diagram of the three-dimensional micro-nano fiber scaffold prepared in Comparative Example 1;

[0036] Fig. 9 This is the appearance of the three-dimensional micro-nano fiber scaffold prepared in Comparative Example 2;

[0037] Fig.10 This is a scanning electron microscope image of the upper surface of the three-dimensional micro-nano fiber scaffold prepared in Comparative Example 1;

[0038] Fig.11 This is a scanning electron microscope image of the upper surface of the three-dimensional micro-nano fiber scaffold prepared in Comparative Example 2;

[0039] Fig.12 The compressive stress-strain result diagram of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared in Examples 1 and 2 and the three-dimensional micro-nano fiber scaffold prepared in Comparative Examples 1 and 2;

[0040] Fig.13This is a graph showing the compression modulus results of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared in Examples 1-2 and the three-dimensional micro-nano fiber scaffold prepared in Comparative Examples 1-2. DETAILED DESCRIPTION

[0041] The present invention provides a method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold. The schematic diagram of the preparation process is as follows: Figure 1 As shown, the following steps are included:

[0042] A hydrophobic medical polymer material, a hydrophilic medical polymer material and a solvent are mixed to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning to obtain a micro-nano fiber membrane;

[0043] The micro-nano fiber membrane is foamed with a foaming liquid to obtain a three-dimensional micro-nano fiber scaffold;

[0044] The three-dimensional micro-nano fiber scaffold was injected with sol B and then freeze-dried to obtain a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold.

[0045] In the present invention, the hydrophobic medical polymer material preferably includes one or more of polycaprolactone (PCL), polylactic acid (PLA), poly-L-lactic acid (PLLA), poly-D-lactic acid (PDLA), polylactic acid-glycolic acid copolymer (PLGA), and poly-L-lactide-caprolactone (PLCL), further preferably one or more of PCL, PLA, and PLGA, and more preferably PCL.

[0046] In the present invention, the hydrophilic medical polymer material preferably includes one or more of collagen, gelatin, silk fibroin, chitosan, hyaluronic acid, polyvinyl alcohol (PVA), polyethylene glycol (PEG), and polyethylene oxide (PEO), further preferably one or more of gelatin, silk fibroin, hyaluronic acid, and PVA, and more preferably gelatin.

[0047] In the present invention, the solvent preferably includes one or more of hexafluoroisopropanol, dichloromethane, and chloroform, more preferably hexafluoroisopropanol or dichloromethane, and more preferably hexafluoroisopropanol.

[0048] In the present invention, the mass ratio of the hydrophobic medical polymer material to the hydrophilic medical polymer material is preferably 0-99:1-100, more preferably 2-30:1-20, and even more preferably 4:1.

[0049] In the present invention, the total mass concentration of the hydrophobic medical polymer material and the hydrophilic medical polymer material in the spinning solution is preferably 0.08 to 0.12 g / mL, more preferably 0.09 to 0.11 g / mL, and even more preferably 0.1 g / mL.

[0050] In the present invention, the parameters of the electrospinning are: the spinning voltage is preferably 17-20 kv, more preferably 19-20 kv, and more preferably 20 kv; the spinning distance is preferably 12-16 cm, more preferably 14-16 cm, and more preferably 16 cm; the injection speed is preferably 1-1.5 mL / h, more preferably 1.2-1.5 mL / h, and more preferably 1.5 mL / h; the needle model is preferably 21-24 G, more preferably 21-23 G, and more preferably 21 G; the receiving drum speed is preferably 100-500 rpm, more preferably 200-400 rpm, and more preferably 300 rpm.

[0051] In the present invention, after the electrospinning is completed, vacuum drying at 37° C. for 24 hours is also included.

[0052] In the present invention, the foaming liquid preferably includes sol A and sodium borohydride.

[0053] In the present invention, the sol A preferably includes one or more of gelatin sol, GelMA sol, and hyaluronic acid sol, more preferably gelatin sol or hyaluronic acid sol, and more preferably gelatin sol.

[0054] In the present invention, the mass concentration of the sol A is preferably 0.01 to 5%, more preferably 1 to 5%, and even more preferably 5%.

[0055] In the present invention, the concentration of sodium borohydride in the foaming liquid is preferably 0.1 to 1 mol / L, more preferably 0.4 to 0.7 mol / L, and even more preferably 0.5 mol / L.

[0056] In the present invention, the foaming time is preferably 10 to 60 minutes, more preferably 12 to 30 minutes, and even more preferably 15 minutes.

[0057] In the present invention, the step of washing with water is further included after the foaming is completed.

[0058] In the present invention, the injection filling method is: using a syringe to extract sol B and then injecting it into the three-dimensional micro-nano fiber scaffold; the needle model of the syringe is preferably 18-25G, more preferably 20-24G, and more preferably 22G.

[0059] In the present invention, the volume ratio of the sol B to the volume of the three-dimensional micro-nano fiber scaffold is preferably 1-5 mL: 1-4 cm 3 , more preferably 1-2 mL: 3-4 cm 3 , more preferably 1mL:4cm 3 .

[0060] In the present invention, the sol B preferably includes one or more of gelatin sol, GelMA sol, silk fibroin sol, hyaluronic acid sol, and chitosan sol, further preferably one or more of gelatin sol, hyaluronic acid sol, and chitosan sol, and more preferably gelatin sol.

[0061] In the present invention, the mass concentration of the sol B is preferably 0.1 to 20%, more preferably 5 to 15%, and even more preferably 10%.

[0062] In the present invention, the freeze-drying includes freezing and freeze-drying; the freezing temperature is preferably -20°C; the freezing time is preferably 12 to 16 hours, more preferably 12 to 14 hours, and more preferably 12 hours; the freeze-drying temperature is preferably -50 to -80°C, more preferably -60 to -80°C, and more preferably -80°C; the freeze-drying time is preferably 24 to 48 hours, more preferably 28 to 45 hours, and more preferably 40 hours.

[0063] The present invention also provides a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared by a method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold.

[0064] The present invention also provides an application of a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold in biomedical materials.

[0065] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0066] Example 1

[0067] This embodiment provides a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the preparation method of which includes the following steps:

[0068] (1) Weigh 1.6 g PCL (molecular weight of 80,000) and 0.4 g gelatin (Gel, derived from pig skin) and dissolve them in 20 mL hexafluoroisopropanol (HFIP) to obtain a uniformly dispersed PCL / Gel spinning solution with a total mass concentration of 0.1 g / mL; divide 20 mL of PCL / Gel spinning solution into two 10 mL syringes and perform electrospinning by a counter-spraying method; the electrospinning parameters are set as follows: spinning voltage 20 kV, spinning distance 16 cm, injection speed 1.5 mL / h, needle model 21G, and receiving drum speed 300 rpm; the collected membrane is vacuum dried at 37 °C for 24 h to obtain a micro-nano fiber membrane;

[0069] (2) Weighing 2.5 g of gelatin and dissolving it in 50 mL of ultrapure water, stirring it magnetically at 40° C. for 30 min to fully dissolve the gelatin, and then cooling it at room temperature for 1 h to obtain a gelatin sol with a mass concentration of 5%; adding sodium borohydride to the gelatin sol to make its concentration 0.5 mol / L to obtain a foaming solution; placing the micro-nano fiber membrane in the foaming solution, foaming for 15 min, and then taking it out and rinsing it with deionized water three times to remove the residual sodium borohydride, thereby obtaining a three-dimensional micro-nano fiber scaffold;

[0070] (3) Weigh 5 g of gelatin and dissolve it in 50 mL of ultrapure water. Stir it with a magnetic stirrer at 40°C for 30 min to fully dissolve the gelatin. Then cool it at room temperature for 1 h to obtain a gelatin sol with a mass concentration of 10%. Use a 22G syringe to extract 1 mL of the gelatin sol and inject it into a 4 cm 3 The filling is completed in the three-dimensional micro-nano fiber scaffold; then it is frozen in a -20℃ refrigerator for 16 hours, and then transferred to a vacuum freeze dryer and freeze-dried at -80℃ for 40 hours to obtain a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold.

[0071] The appearance of the micro-nano fiber membrane obtained in step (1) of Example 1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the thickness of the micro-nano fiber membrane obtained by electrospinning is in the range of 150 to 200 μm.

[0072] The appearance of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared in Example 1 is as follows: Figure 3 As shown, the appearance after pressing is as shown Figure 4 As shown. Figure 3 and Figure 4 It can be seen that the thickness of the integrated three-dimensional micro-nano fiber scaffold can reach 1 cm, and the thickness can be as low as 1 mm after pressing. When the present invention is used, the thickness can be flexibly and conveniently adjusted by pressing to meet different medical needs.

[0073] The scanning electron microscope image of the micro-nano fiber membrane obtained in step (1) of Example 1 is as follows: Figure 5 As shown, the scanning electron microscope images of the upper surface and the interior of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared in Example 1 are as follows Figure 6 and Figure 7 As shown. Figure 5 to Figure 7 It can be seen that the three-dimensional micro-nano fiber material and the freeze-dried scaffold form a continuous integrated interpenetrating network structure with good integrity and not easy to delaminate.

[0074] Example 2

[0075] This embodiment provides a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the preparation method of which includes the following steps:

[0076] (1) Weigh 1.2 g PCL (molecular weight of 80,000) and 0.8 g gelatin (Gel, derived from pig skin) and dissolve them in 20 mL hexafluoroisopropanol (HFIP) to obtain a uniformly dispersed PCL / Gel spinning solution with a total mass concentration of 0.1 g / mL; divide 20 mL of PCL / Gel spinning solution into two 10 mL syringes and perform electrospinning by a counter-spraying method; the electrospinning parameters are set as follows: spinning voltage 20 kV, spinning distance 16 cm, injection speed 1.5 mL / h, needle model 22G, and receiving drum speed 500 rpm; the collected membrane is vacuum dried at 37 °C for 24 h to obtain a micro-nano fiber membrane;

[0077] (2) Weighing 2.5 g of gelatin and dissolving it in 50 mL of ultrapure water, stirring it magnetically at 40° C. for 30 min to fully dissolve the gelatin, and then cooling it at room temperature for 1 h to obtain a gelatin sol with a mass concentration of 5%; adding sodium borohydride to the gelatin sol to make its concentration 0.5 mol / L to obtain a foaming solution; placing the micro-nano fiber membrane in the foaming solution, foaming for 10 min, and then taking it out and rinsing it with deionized water three times to remove the residual sodium borohydride, thereby obtaining a three-dimensional micro-nano fiber scaffold;

[0078] (3) Weigh 2.5 g of gelatin and dissolve it in 50 mL of ultrapure water. Stir it with a magnetic stirrer at 40°C for 30 min to fully dissolve the gelatin. Then cool it at room temperature for 1 h to obtain a gelatin sol with a mass concentration of 5%. Use a 25G syringe to extract 1 mL of the gelatin sol and inject it into a 4 cm 3 The filling is completed in the three-dimensional micro-nano fiber scaffold; then it is frozen in a -20℃ refrigerator for 16 hours, and then transferred to a vacuum freeze dryer and freeze-dried at -80℃ for 40 hours to obtain a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold.

[0079] Example 3

[0080] This embodiment provides a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the preparation method of which includes the following steps:

[0081] (1) Weigh 1.92 g PCL (molecular weight of 80,000) and 0.48 g gelatin (Gel, derived from pig skin) and dissolve them in 20 mL of hexafluoroisopropanol (HFIP) to obtain a uniformly dispersed PCL / Gel spinning solution with a total mass concentration of 0.12 g / mL; divide 20 mL of PCL / Gel spinning solution into two 10 mL syringes and perform electrospinning by a counter-spraying method; the electrospinning parameters are set as follows: spinning voltage 20 kV, spinning distance 16 cm, injection speed 1.5 mL / h, needle model 21G, and receiving drum speed 400 rpm; the collected membrane is vacuum dried at 37 °C for 24 h to obtain a micro-nano fiber membrane;

[0082] (2) Weighing 2.5 g of gelatin and dissolving it in 50 mL of ultrapure water, stirring it magnetically at 40° C. for 30 min to fully dissolve the gelatin, and then cooling it at room temperature for 1 h to obtain a gelatin sol with a mass concentration of 5%; adding sodium borohydride to the gelatin sol to make its concentration 0.5 mol / L to obtain a foaming solution; placing the micro-nano fiber membrane in the foaming solution, foaming for 10 min, and then taking it out and rinsing it with deionized water three times to remove the residual sodium borohydride, thereby obtaining a three-dimensional micro-nano fiber scaffold;

[0083] (3) Weigh 0.1 g of hyaluronic acid and dissolve it in 10 mL of ultrapure water. Stir magnetically at room temperature for 24 h to obtain a hyaluronic acid sol with a mass concentration of 1%. Use an 18G syringe to extract 1 mL of hyaluronic acid sol and inject it into a 4 cm 3 The filling is completed in the three-dimensional micro-nano fiber scaffold; then it is frozen in a -20℃ refrigerator for 16 hours, and then transferred to a vacuum freeze dryer and freeze-dried at -80℃ for 40 hours to obtain a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold.

[0084] Example 4

[0085] This embodiment provides a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, the preparation method of which includes the following steps:

[0086] (1) Weigh 1.44 g PCL (molecular weight of 80,000) and 0.96 g gelatin (Gel, derived from pig skin) and dissolve them in 20 mL hexafluoroisopropanol (HFIP) to obtain a uniformly dispersed PCL / Gel spinning solution with a total mass concentration of 0.12 g / mL; divide 20 mL of PCL / Gel spinning solution into two 10 mL syringes and perform electrospinning by a counter-spraying method; the electrospinning parameters are set as follows: spinning voltage 18 kV, spinning distance 16 cm, injection speed 1.5 mL / h, needle model 24G, and receiving drum speed 500 rpm; the collected membrane is vacuum dried at 37 °C for 24 h to obtain a micro-nano fiber membrane;

[0087] (2) Weighing 2.5 g of gelatin and dissolving it in 50 mL of ultrapure water, stirring it magnetically at 40° C. for 30 min to fully dissolve the gelatin, and then cooling it at room temperature for 1 h to obtain a gelatin sol with a mass concentration of 5%; adding sodium borohydride to the gelatin sol to make its concentration 0.5 mol / L to obtain a foaming solution; placing the micro-nano fiber membrane in the foaming solution, foaming for 10 min, and then taking it out and rinsing it with deionized water three times to remove the residual sodium borohydride, thereby obtaining a three-dimensional micro-nano fiber scaffold;

[0088] (3) Weigh 0.05 g of hyaluronic acid and dissolve it in 10 mL of ultrapure water. Stir magnetically at room temperature for 24 h to obtain a hyaluronic acid sol with a mass concentration of 0.5%. Use a 22G syringe to extract 1 mL of hyaluronic acid sol and inject it into a 4 cm 3 The filling is completed in the three-dimensional micro-nano fiber scaffold; then it is frozen in a -20℃ refrigerator for 16 hours, and then transferred to a vacuum freeze dryer and freeze-dried at -80℃ for 40 hours to obtain a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold.

[0089] Comparative Example 1

[0090] This comparative example provides a three-dimensional micro-nano fiber scaffold, and the preparation method thereof comprises the following steps:

[0091] (1) The preparation of the micro-nano fiber membrane refers to step (1) of Example 1;

[0092] (2) Weigh 2.5 g of gelatin and dissolve it in 50 mL of ultrapure water. Stir magnetically at 40°C for 30 min to fully dissolve the gelatin, and then cool at room temperature for 1 h to obtain a gelatin sol with a mass concentration of 5%; add sodium borohydride to the gelatin sol to make its concentration 0.5 mol / L to obtain a foaming solution; place the micro-nano fiber membrane in the foaming solution, foam for 15 min, then take it out and rinse it three times with deionized water to remove residual sodium borohydride; then freeze it in a refrigerator at -20°C for 16 h, and then transfer it to a vacuum freeze dryer and freeze-dry it at -80°C for 40 h to obtain a three-dimensional micro-nano fiber scaffold.

[0093] Comparative Example 2

[0094] This comparative example provides a three-dimensional micro-nano fiber scaffold, and the preparation method thereof comprises the following steps:

[0095] (1) The preparation of the micro-nano fiber membrane refers to step (1) of Example 1;

[0096] (2) Sodium borohydride was added to 50 mL of ultrapure water to a concentration of 0.5 mol / L to obtain a foaming solution; the micro-nano fiber membrane was placed in the foaming solution and foamed for 15 min, then taken out and rinsed three times with deionized water to remove residual sodium borohydride; then, it was frozen in a -20°C refrigerator for 16 h, and then transferred to a vacuum freeze dryer and freeze-dried at -80°C for 40 h to obtain a three-dimensional micro-nano fiber scaffold.

[0097] The appearance of the three-dimensional micro-nano fiber scaffold prepared in Comparative Examples 1 and 2 is shown in FIG. Figure 8 and Fig. 9 As shown. Figure 8 It can be seen that the three-dimensional micro-nano fiber scaffold prepared by using only sol as the foaming medium without injection filling has a slight collapse, but no delamination occurs. Fig. 9It can be seen that the three-dimensional micro-nano fiber scaffold prepared by using only sodium borohydride as the foaming liquid and without injection filling has serious collapse and obvious stratification. The mechanical properties of both are poor.

[0098] The scanning electron microscope images of the upper surface of the three-dimensional micro-nano fiber scaffold prepared in Comparative Examples 1 and 2 are as follows: Fig.10 and Fig.11 As shown. Fig.10 It can be seen that the sol, as a foaming medium, strengthens the connection between fibers and initially forms a dense three-dimensional network structure. Fig.11 It can be seen that the fiber stacking distribution is loose and the interaction between fibers is weak, resulting in poor mechanical properties.

[0099] The compressive stress-strain results of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffolds prepared in Examples 1 and 2 and the three-dimensional micro-nano fiber scaffolds prepared in Comparative Examples 1 and 2 are shown in the figure. Fig.12 As shown. Fig.12 It can be seen that the present invention utilizes a foaming liquid containing a sol to foam to obtain a three-dimensional micro-nano fiber scaffold to provide preliminary mechanical support for the scaffold, and then fills the sol and freeze-dries to obtain an integrated three-dimensional micro-nano fiber scaffold. Compared with Comparative Example 1 in which only the sol is used as the foaming medium without injection filling and Comparative Example 2 in which a single sodium borohydride is used as the foaming liquid without injection filling, the mechanical compressive strength of the three-dimensional micro-nano fiber scaffold is significantly enhanced.

[0100] The compression modulus results of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffolds prepared in Examples 1 and 2 and the three-dimensional micro-nano fiber scaffolds prepared in Comparative Examples 1 and 2 are shown in FIG. Fig.13 As shown. Fig.13 It can be seen that the integrated three-dimensional micro-nano fiber scaffold prepared by the method of the present invention has improved compression resistance and stability, and is suitable for applications under high load conditions.

[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold, characterized in that: The following steps are involved: A hydrophobic medical polymer material, a hydrophilic medical polymer material and a solvent are mixed to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning to obtain a micro-nano fiber membrane; The micro-nano fiber membrane is foamed with a foaming liquid to obtain a three-dimensional micro-nano fiber scaffold; The three-dimensional micro-nano fiber scaffold is injected with sol B and then freeze-dried to obtain a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold; Wherein, the foaming liquid comprises sol A and sodium borohydride; the sol A comprises one or more of gelatin sol, GelMA sol and hyaluronic acid sol; The sol B includes one or more of gelatin sol, GelMA sol, silk fibroin sol, hyaluronic acid sol, and chitosan sol.

2. The method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold according to claim 1, characterized in that: The hydrophobic medical polymer material includes one or more of polycaprolactone, polylactic acid, poly-L-lactic acid, poly-D-lactic acid, polylactic acid-glycolic acid copolymer, and poly-L-lactide-caprolactone; the hydrophilic medical polymer material includes one or more of collagen, gelatin, silk fibroin, chitosan, hyaluronic acid, polyvinyl alcohol, polyethylene glycol, and polyethylene oxide.

3. The method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold according to claim 2, characterized in that: The parameters of the electrospinning are: spinning voltage of 17-20 kV; spinning distance of 12-16 cm; injection speed of 1-1.5 mL / h; needle model of 21-24 G; receiving roller speed of 100-500 rpm.

4. The method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold according to claim 1, characterized in that: The mass concentration of the sol A is 0.01-5%; the concentration of sodium borohydride in the foaming liquid is 0.1-1 mol / L.

5. The method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold according to claim 1 or 4, characterized in that: The foaming time is 10 to 60 minutes.

6. The method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold according to claim 5, characterized in that: The mass concentration of the sol B is 0.1-20%.

7. The method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold according to claim 6, characterized in that: The injection filling method is: using a syringe to extract sol B and then injecting it into the three-dimensional micro-nano fiber scaffold; the volume ratio of the sol B to the volume of the three-dimensional micro-nano fiber scaffold is 1-5 mL: 1-4 cm 3 .

8. The method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold according to claim 7, characterized in that: The freeze drying includes freezing and freeze drying; the freezing temperature is -20°C; the freezing time is 12 to 16 hours; the freeze drying temperature is -50 to -80°C; and the freeze drying time is 24 to 48 hours. 9 . A mechanically enhanced integrated three-dimensional micro-nano fiber scaffold prepared by the method for preparing a mechanically enhanced integrated three-dimensional micro-nano fiber scaffold as described in any one of claims 1 to 8 .

10. Use of the mechanically enhanced integrated three-dimensional micro-nano fiber scaffold according to claim 9 in biomedical materials.

Citation Information

Patent Citations

  • Method for preparing micro-nano fiber three-dimensional network by expansion process

    CN113073423A

  • Articular cartilage scaffold and preparation method thereof

    CN113750291A

  • Injectable three-dimensional nano fiber scaffolds and method for preparing the same

    KR1020180018000A

  • Nanofiber structures and methods of use thereof

    US20200164107A1